1991
DOI: 10.1016/0266-3538(91)90041-m
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bevel and tulip triggered pultruded tubes for energy absorption

Abstract: The crushing behavior of E-glass~polyester and E-glass/vinyl ester pultruded tubes has been found to be significantly different for tulip triggered specimens as compared with bevel triggered specimens. Up to 100% more energy per unit weight was absorbed by tulip triggered tubes. In addition, the crushing was more controlled and predictable with the tulip trigger. The morphology of the material in the crushing zone differed in the amount and the pattern of fracture. The fracture pattern and crushing behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…(2) delamination or inter-laminar crack growth, Mode II fracture; (3) axial splitting of the middle layer; (4) lamina bundle bending damage and fracture; (5) friction between the platen and the crush zone; (6) friction between the debris wedge and the interior layer; (7) friction between the debris wedge and the middle layer; (8) friction between the middle layer and the exterior layer; and (9) friction between adjacent lamina due to sliding.…”
Section: Energy Dissipation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) delamination or inter-laminar crack growth, Mode II fracture; (3) axial splitting of the middle layer; (4) lamina bundle bending damage and fracture; (5) friction between the platen and the crush zone; (6) friction between the debris wedge and the interior layer; (7) friction between the debris wedge and the middle layer; (8) friction between the middle layer and the exterior layer; and (9) friction between adjacent lamina due to sliding.…”
Section: Energy Dissipation Mechanismsmentioning
confidence: 99%
“…Similar to single-chamfer-triggered pattern, applying this trigger pattern is an efficient way to weaken the peak load, reduce the probability of catastrophic failure and avoid unstable crush. Thornton, Czaplicki and Robertson [8,25] have found that the tulip trigger, incorporated at one end of the square tubes, affords an improvement in the crush stability and nearly 100% increase of the specific energy absorption (SEA) as compared with the bevel trigger. An inner-type jig [28] progressive crushing mode and improve the energy absorption capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axial crushing of E-glass/polyester tubes and E-glass/vinyl ester tubes [11] has shown that certain parameters must be controlled for crushing to proceed satisfactorily. Of primary importance is the control of crack behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Rabiee, H. Ghasemnejad graphite/epoxy and Kevlar/epoxy square cross section tubes. Czaplicki et al [85] reported that significantly higher energy absorption of tulip-triggered specimens were observed compared to bevel triggered specimens of the same geometry and material.…”
Section: Structural Geometrymentioning
confidence: 99%